Cure Kinetics and Activation Energy Studies of Modified Bismaleimide Resins. (28th March 2012) - Chandran, M. Satheesh; Krishna, M.; Rai, Sheshappa; Krupashankara, M. S.; Salini, K.
Abstract : The cure kinetics and activation energy (Ea) of bismaleimide homopolymer and modified bismaleimide resin systems with different chain extenders were investigated. The bismaleimide resin under investigation was bismaleimidodiphenyl methane (BMPM) and the chain extenders were (i) O-O′ diallyl bisphenol A (DABA) and (ii) methylenedianiline (MDA). Dynamic multiheating DSC method was used to study the kinetics of the curing process. Activation energies were determined for both unmodified and modified resins from nonisothermal multiheating rate DSC tests by using Ozawa and Kissinger models. Activation energy for BMPM homopolymer increased from 95 kJ/mol to 125 kJ/mol as a function of conversion. For the MDA-modified system the activation energy was independent of percentage conversion, at 108 kJ/mol. In the case of DABA-modified bismaleimide the activation energy increased steadily at 6 kJ/mol from 10 to 100% conversion.